2019
DOI: 10.1177/1359104519846194
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions of youths with functional disorders and their parents: An interpretative phenomenological analysis study

Abstract: Background: Functional disorders, defined as disorders with no clear medical explanation, are common and impose a significant burden on youths, their families, healthcare services and society as a whole. Currently, the literature describes resistance among patients and their families towards psychological symptom explanations and treatments. More knowledge about the thoughts and understandings of youths with functional disorders and their parents is needed. The aim of this study was to explore the illness perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Known maintaining factors include negative illness perceptions (e.g. single cause attribution of symptom, no sense of control and long expectancy of symptoms) [14][15][16] and maladaptive illness behaviours (e.g. avoidance, control and 'all-or-nothing' behaviour) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Known maintaining factors include negative illness perceptions (e.g. single cause attribution of symptom, no sense of control and long expectancy of symptoms) [14][15][16] and maladaptive illness behaviours (e.g. avoidance, control and 'all-or-nothing' behaviour) [17].…”
Section: Introductionmentioning
confidence: 99%
“…The previous papers from the overall study (Figure 1), conducted at the point of referral, found resistance and scepticism among parents and youths towards SFT (Hulgaard et al, 2019a;Hulgaard et al, 2019b).…”
Section: Discussionmentioning
confidence: 88%
“…As the study was conducted in a secondary public healthcare setting, the SFT could only be accessed through referral by a paediatric department, and while all of the included families had accepted referral, none of them had actively sought SFT treatment and some families had critical preconceptions of the family therapy format (Hulgaard et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations